Patient perceptions of the relationship between food insecurity and eating disorder treatment: A qualitative exploration. Issue 3 (31st December 2021) - Frayn, Mallory; Trainor, Claire; Lin, Mandy; Pitts, Alexandra; Drexler, Sarah A.; Patarinski, Anna Gabrielle G.; Juarascio, Adrienne
Abstract: Introduction: Independently, food insecurity (FI) and binge‐spectrum eating disorders (B‐ED) are widespread problems; moreover, FI is associated with elevated binge‐eating symptoms. However, extant research has not explored how FI may contribute to the development of B‐ED symptoms, nor potential impacts of FI on eating disorder treatment. Method: This study aimed to qualitatively examine (1) mechanisms by which FI impacts B‐ED development and maintenance, (2) effects of past and/or present FI on ED treatment, and (3) participant recommendations for addressing FI in future B‐ED treatment. Fourteen individuals who completed B‐ED treatment and endorsed FI completed a 30‐min interview about their experiences. Results: Participants reported that FI contributed to binge eating by maintaining dietary restraint‐binge‐eating cycle and by leading them to use food as a coping mechanism or for emotional comfort, both in past and present situations. Present FI interfered with treatment, particularly with adhering to treatment recommendations and food purchasing choices, however, participants did not report any impact of past FI on B‐ED treatment. Participants reported that rarely was FI addressed as part of treatment; most participants suggested that future treatments work to (1) assess and problem solve present FI to minimize interference and (2) assess and understand the influence of past FI on current symptoms to validate the function of behavior. Discussion: These findings provide qualitative support that FI may reinforce B‐ED symptoms and present FI may interfere with treatment. This study emphasizes the need for assessment and consideration of FI as a factor when treating individuals with B‐EDs.